Improving Sharia Financial Literacy in Indonesia on A Digital Basis with the Introduction of the Sharia Non-Bank Finance Industry (Iknb) and Its Instruments - Difa Zahrah Zakiyah; Shafa Athaya; Alif Kahlil Gibran (Journal of Islamic Economy and Community Engagement, 2023)
The Islamic non-bank financial industry has experienced significant growth in recent years. In the context of an increasingly complex modern economy, this industry has played an important role in facilitating financial activities that comply with sharia principles. This journal aims to contribute to existing knowledge by presenting research papers, case studies, and theoretical discussions relating to the non-bank Islamic finance industry, while the purpose of the service is to increase public literacy towards Sharia IKNB. The method used in carrying out this community service activity is semi-structured and discussion, which includes material using short videos uploaded on social media with a discussion model in the form of asking questions and statements through the comment’s column. That way the results obtained from this service activity are the participant's literacy level towards IKNB and Sharia IKNB indicating that on average new participants understand the concept of Sharia IKNB.